Individual‐ and hospital‐level factors associated with epidermal necrolysis mortality: a nationwide multilevel study, France, 2012–2016. (1st April 2020) - Traikia, C.; Hua, C.; Le Cleach, L.; de Prost, N.; Hemery, F.; Bettuzzi, T.; Chosidow, O.; Wolkenstein, P.; Ingen‐Housz‐Oro, S.; Sbidian, E.
Summary: Background: Epidermal necrolysis (EN) is a rare and life‐threatening condition. Objectives: To assess whether admitting hospital characteristics and interhospital transfer are associated with mortality due to EN. Methods: We studied the French nationwide hospital discharge database (retrospective national cohort). All patients admitted during 2012–2016 with a code for EN in the International Classification of Diseases, 10th Revision, were eligible. We extracted data on the patients (age, sex, intensive care unit admission, comorbidities) and hospitals (private proprietary vs. public, nonteaching or teaching; and number of admissions for EN as a proxy for experience). Multivariable analysis was used to identify independent predictors of in‐hospital mortality with mixed logistic regression. Results: We identified 991 patients (467 male; mean age 52·7 ± 23 years). They were admitted to 300 different hospitals, including teaching hospitals (25% of hospitals) for around half of the patients. Overall, 597 patients (60%) had a diagnosis of Stevens–Johnson syndrome (SJS), 171 (17%) had SJS/toxic epidermal necrolysis (TEN) overlap and 223 (23%) had TEN. In total, 109 (11%) patients died: nine (2%) with SJS, 26 (15%) with SJS/TEN overlap and 74 (33%) with TEN. The in‐hospital mortality rate was lower in centres with vs. without substantial EN experience – odds ratio for one supplemental EN admission in a department 0·5 (95% confidence interval 0·3–1·0); P = 0·05 – even after adjusting for potentially relevant individual risk factors. We found no significant association between mortality and interhospital transfer. Conclusions: Our findings highlight increased survival of patients with EN in centres with a high volume of EN procedures. If confirmed in other settings, these findings reinforce the importance of expertise in early diagnosis and management of this condition. What's already known about this topic? Epidermal necrolysis (EN) is a rare and life‐threatening condition. At the individual level, risk factors for in‐hospital mortality have been identified. Few studies have examined the association between hospital characteristics and EN mortality, with special attention to referral hospitals. What does this study add? Short‐term mortality rates were lower for patients in centres with EN experience than in centres without EN experience, after adjusting for known risk factors. We found no association between interhospital transfer and survival. If confirmed in other settings, these findings support the early transfer of patients with suspected or diagnosed EN to centres with experience, where a multidisciplinary approach can be implemented by experienced healthcare professionals, to maximize short‐term survival.